Experimental Study for Commercial Fertilizer NPK (20:20:20+TE N: P: K) in Microalgae Cultivation at Different Aeration Periods - AL-Mashhadani, Mahmood K. H.; Khudhair, Entisar Mohsin (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Recently, microalgae have become a promising source in the production of biofuel. However, the cost of production is still the main obstacle to develop of this type of source. Although there are many extensive studies on the requirements provided for the cultivation of the microalgae, the study of the process, via the variables that affect the cultivation of microalgae, being still one of the important tasks to improve the production of biofuel. The present article is a serious attempt to investigate of use commercial fertilizer NPK (20:20:20+TE N: P: K) as considered a cheap nutrient medium in growth Chlorella vulgaris by comparison with traditional nutrient (Chu.10 medium). In addition, the current study addresses effect of different sparging periods of filtered air on the microalgae production. The experimental data showed that the use of the NPK fertilizer as cultivation medium in Chlorella vulgaris culture gives more growth rate of microalgae than that produced if the cultivation process was operated with Chu.10 medium. For example the maximum biomass concentration reaches to 0.3249 g L-1 when cultivated in NPK fertilizer, whereas reached to 0.212 g L-1 for cells cultivated in Chu.10 medium. In addition, the results proved that the aeration system in the cultivation can plays an important role in the activity of the microalgae with NPK medium, since it creates a convenient environment with low concentration of oxygen in the medium. The study showed that increasing aeration period for such a type of microalgae increases the growth rate.